Gaining insight into the catalysis by GH20 lacto-N-biosidase using small molecule inhibitors and structural analysis. Issue 81 (27th August 2015) - Hattie, Mitchell; Ito, Tasuku; Debowski, Aleksandra W.; Arakawa, Takatoshi; Katayama, Takane; Yamamoto, Kenji; Fushinobu, Shinya; Stubbs, Keith A.
Abstract : Synthesis and structural analysis of rationally developed inhibitors. Abstract : The synthesis of potent inhibitors for lacto- N -biosidases and X-ray structural characterization of these compounds in complex with Bb LNBase is described.